Macrolactam synthesis via ring-closing alkene-alkene cross-coupling reactions - Maraswami, Manikantha (2022)
Reported herein is a practical method for macrolactam synthesis via a Rh(III)-catalyzed ring closing alkene-alkene cross-coupling reaction. The reaction proceeded via a Rh-catalyzed alkenyl sp2 C-H activation process, which allows access to macrocyclic molecules of different ring sizes. Macrolactams containing a conjugated diene framework could be easily prepared in high chemoselectivities and Z,E stereoselectivities.